Evaluation of a bispidine‐based chelator for gallium‐68 and of the porphyrin conjugate as PET/PDT theranostic agent - Price, Thomas; Yap, Steven Y.; Gillet, Raphaël; Savoie, Huguette; Charbonnière, Loïc J.; Boyle, Ross W.; Nonat, Aline M.; Stasiuk, Graeme J. (Chemistry - A European Journal, 2020)
In this study a bispidine ligand has been applied to the complexation of gallium(III) and radiolabelled with gallium-68 for the first time. Despite its 5-coordinate nature, the resulting complex is stable in serum for over two hours, demonstrating a ligand system well matched to the imaging window of gallium-68 positron emission tomography (PET). To show the versatility of the bispidine ligand and its potential use in PET, the bifunctional chelator was conjugated to a porphyrin, producing a PET/PDT-theranostic, which showed the same level of stability to serum as the non-conjugated gallium-68 complex. The PET/PDT complex killed >90 % of HT-29 cells upon light irradiation at 50 μm. This study shows bispidines have the versatility to be used as a ligand system for gallium-68 in PET.
Keywords: Bispidine; Gallium-68; Porphyrin; Radiochemistry; Theranostic